محاسبة الأجور في المؤسسات العمومية دراسة حالة ديوان المركب المتعدد الرياضات لولاية الوادي - حمزة كهمان; سفيان منيعي; أحمد قده; عماد الدين منصر (جامعة الوادي university of eloued, 2024)
"تهدف الدراسة إلى محاولة توضيح محاسبة الأجور والرواتب في المؤسسات العمومية وأهم أهدافها ، وقد أخذت الدراسة شرح وعرض أهم المفاهيم المتعمقة بالأجور والعناصر المكونة لها. وللإجابة على إشكالية البحث فقد تـم الاعتماد على المنهج الوصفي التحليلي عف طريق ما توفر من معلومات حول متغيرات الدراسة من كتب، مجالات، مذكرات، نصوص قانونية وتنظيمية. وللتفصيل أكثر تـم تقسيـم الدراسة إلى فصلين، الفصل الأول لتغطية مجمل الجوانب النظرية للموضوع والفصل الثاني تطبيقي عن طريق دراسة ميدانية للمفاهيـم النظرية للأجور والمعالجة المحاسبية ليا عبر إسقاطيا على ديوان المركب المتعدد الرياضات بالوادي . ومن خلال دراستنا للأجور ومحاسبتها تبين أن الأجر له عدة مكونات من أجر أساسي، تعويضات، مجموعة من المكافآت والاقتطاعات والتي تنظمها نصوص قانونية وتنظيمية. " "The study aims to attempt to clarify the accounting of wages and salaries in public institutions and their most important objectives. The study included an explanation and presentation of the most important concepts related to wages and their constituent elements. To answer the research problem, the descriptive analytical approach was relied upon through the available information about the study variables, including books, magazines, memos, legal and regulatory texts. For more detail, the study was divided into two chapters, the first chapter to cover all the theoretical aspects of the subject and the second practical chapter through a field study of the theoretical concepts of wages and their accounting treatment by projecting them onto the office of the Multi-Sports Complex in the Valley. Through our study of wages and their accounting, it became clear that wages have several components, including a basic wage, compensation, and a set of bonuses and deductions, which are regulated by legal and regulatory texts"
مذكرة ماستر
Keywords: محاسبة الاجور، المؤسسات العمومية، المردودية، الترقيات. wage accounting; public institutions; cost – effectiveness; promotions.